PENERAPAN KONSEP AIDA DALAM STRATEGI KOMUNIKASI PEMASARAN UNTUK MENINGKATKAN MINAT BELI PRODUK APPLE RESMI DI SIANTAR PONSEL TEUKU UMAR DENPASAR - Sahri Aflah Ramadiansyah; Donny Irza Hariri Effendy; Putri Ekaresty Haes; Jonathan Jacob Paul Latupeirissa (Bajang Institute, 2025)
This study aims to analyze how the AIDA concept (Attention, Interest, Desire, Action) is applied in the marketing communication strategy carried out by SiantarPonsel, a certified smartphone retailer in Denpasar, particularly in promoting Apple products. The study uses a descriptive qualitative approach, with data collected through direct observation, interviews with the store manager, staff members, and customers, as well as documentation of both online and offline promotional activities. The findings show that SiantarPonsel strengthens the Attention stage through window displays, banners, and visual promotional materials; the Interest stage through social media content, product education, and device demonstrations; the Desire stage through interpersonal communication that highlights product authenticity, official warranty, and long-term value; and the Action stage through installment programs, trade-in options, and WhatsApp Broadcasts that encourage purchasing decisions. These strategies help build a strong perception of quality and increase consumer interest in Apple products among local buyers in Denpasar. The study emphasizes the importance of integrating offline and online marketing communication and the role of staff competence in shaping purchasing decisions for premium products.